The effects of skin and core tissue cooling on oxygenation of the vastus lateralis muscle during walking and running - Gagnon, D. D.; Peltonen, J. E.; Rintamäki, H.; Gagnon, S. S.; Herzig, K.-H.; Kyröläinen, H. (Journal of Sports Sciences, 2017)
Skin and core tissue cooling modulates skeletal muscle oxygenation at rest. Whether tissue cooling also influences the skeletal muscle deoxygenation response during exercise is unclear. We evaluated the effects of skin and core tissue cooling on skeletal muscle blood volume and deoxygenation during sustained walking and running. Eleven male participants walked or ran six times on a treadmill for 60 min in ambient temperatures of 22°C (Neutral), 0°C for skin cooling (Cold 1), and at 0°C following a core and skin cooling protocol (Cold 2). Difference between oxy/deoxygenated haemoglobin ([diffHb]: deoxygenation index) and total haemoglobin content ([tHb]: total blood volume) in the vastus lateralis (VL) muscle was measured continuously. During walking, lower [tHb] was observed at 1 min in Cold 1 and Cold 2 vs. Neutral (P<0.05). Lower [diffHb] was seen at 1 and 10 min in Cold 2 vs. Neutral by 13.5 ± 1.2 µM and 15.3 ± 1.4 µM and Cold 1 by 10.4 ± 3.1 µM and 11.1 ± 4.1 µM, respectively (P<0.05). During running, [tHb] was lower in Cold 2 vs. Neutral at 10 min only (P = 0.004). [diffHb] was lower at 1 min in Cold 2 by 11.3 ± 3.1 µM compared to Neutral and by 13.5 ± 2.8 µM compared to Cold 1 (P<0.001). Core tissue cooling, prior to exercise, induced greater deoxygenation of the VL muscle during the early stages of exercise, irrespective of changes in blood volume. Skin cooling alone, however, did not influence deoxygenation of the VL during exercise.